Insider trading and corporate governance: The case of Germany - André Betzer; Erik Theissen (University of Cologne, Centre for Financial Research (CFR), 2007)
We analyze transactions by corporate insiders in Germany. We find that insider trades are associated with significant abnormal returns. Insider trades that occur prior to an earnings announcement have a larger impact on prices. This result provides a rationale for the UK regulation that prohibits insiders from trading prior to earnings announcements. Both the ownership structure and the accounting standards used by the firm affect the magnitude of the price reaction. The position of the insider within the firm has no effect, which is inconsistent with the informational hierarchy hypothesis.
Keywords: G14; G30; G32; 330; Insider trading; directors' dealings; corporate governance